2020
DOI: 10.2131/jts.45.423
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of microRNA expression profiling during paraquat-induced injury of murine lung alveolar epithelial cells

Abstract: Paraquat (PQ) as a non-selective heterocyclic herbicide, has been applied worldwide for over a few decades. But PQ is very harmful to humans and rodents. The lung is the main target organ of PQ poisoning. It is an important event that lung epithelial cells are injured during PQ-induced acute lung injury and pulmonary fibrosis. As a regulator of mRNA expression, microRNA (miRNA) may play an important role in the progress. Our study was to investigate the mechanisms of PQ-induced injury of pulmonary epithelial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Microarray technology helps determine mRNA profiles and provides a comprehensive and systematic analysis of disease processes, including those involved in pulmonary fibrosis [ 5 ]. In addition, some studies have revealed that PQ intoxication may cause alterations at the genome level [ 5 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microarray technology helps determine mRNA profiles and provides a comprehensive and systematic analysis of disease processes, including those involved in pulmonary fibrosis [ 5 ]. In addition, some studies have revealed that PQ intoxication may cause alterations at the genome level [ 5 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Microarray technology helps determine mRNA profiles and provides a comprehensive and systematic analysis of disease processes, including those involved in pulmonary fibrosis [ 5 ]. In addition, some studies have revealed that PQ intoxication may cause alterations at the genome level [ 5 8 ]. Thus, integrative analyses of genes and pathways associated with lung fibrosis may provide insights into potential therapeutic targets and diagnostic biomarkers for PQ-induced pulmonary fibrosis.…”
Section: Introductionmentioning
confidence: 99%